Project Based Learning: A Solution to Improve Students' Learning Achievement - Chrustiana, Tin Indria; Rahmawati, Dwi; Anwar, Rahmad Bustanul; Fauzi, Irsyad (International Journal of Multidisciplinary Research of Higher Education, 2025)
Effective and quality education is essential in improving students' learning achievement. However, conventional learning methods often cannot meet the diverse learning needs of students. Therefore, innovative and effective learning methods are needed, such as project-based learning. This study aims to analyze how the effect of project-based learning model implementation on students' social arithmetic learning achievement. This research uses quantitative methods with the type of classroom action research, the data source is taken from thirty-four students at one of the junior high schools in Indonesia. In this study, the data analysis tool used was the Statistical Package for the Social Sciences to process quantitative data on students' test results. The analysis was carried out by calculating the average value, percentage of learning completeness, and paired sample t-test to see the improvement of learning outcomes between cycle I and cycle II. The results showed that the application of Project-Based Learning showed a significant increase in the students' completeness criteria, from 47.06% in the pre-cycle, increased to 67.65% in Cycle I, and reached 94.12% in Cycle II. This research is expected to help educators in choosing effective and contextual learning methods to create interesting, relevant, and meaningful learning experiences for students.